Czech cultural standards from Tajik perspective in work environment - Hakim, Pariso; Křečková Kroupová, Zuzana, 1972-; Semenenko, Vadim; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
This Bachelor’s thesis is devoted to the identification of Czech cultural standards from the Tajik perspective in the work environment. The main goal is to investigate cultural standards through Tajik working people’s view. In the theoretical part studies of G.Hofstede, F.Trompenaars, A.Thomas about cultural standards and cultural dimensions have been described. Further Czech and Tajik cultures are introduced including their values and features. In the practical part, the author describes and explains seven cultural standards that have been investigated during the qualitative research. This is followed by the comparison and explanation of the theoretical basis of Czech culture and identified Czech cultural standards. Finally, the author gives a list of the recommendations for Tajiks coming to the Czech Republic to work with the Czech people.
Vedoucí práce: Zuzana Křečková Kroupová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses